2018
DOI: 10.1021/acs.orglett.8b02668
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Arylzincation of Alkynes: Ligand Control of 1,4-Migration Selectivity

Abstract: The addition of arylzinc reagents ArZnCl 1 to alkynes 2 was found to be catalyzed by rhodium complexes in the presence of a catalytic amount of zinc chloride. The selectivity in giving 2-arylalkenylzinc species 3 or ortho-alkenylarylzinc species 4, the latter of which is generated through 1,4-Rh migration from alkenyl to aryl in the catalytic cycle, is controlled by the ligands on rhodium. Ligands cod and binap gave 3 and 4, respectively, with high selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The reaction was monitored by D 2 O quenching. With BINAP as a ligand, the reaction gave aryl‐D product 80 with 99% selectivity; meanwhile, the formation of vinyl‐D product 79 was favored with ligand (1 Z ,5 Z )‐cycloocta‐1,5‐diene (COD) (Scheme ) . It was reasoned that the transmetallation of M59 with ZnCl 2 would give M60 , a product without undergoing 1,4‐Rh migration when COD was used as the ligand.…”
Section: 4‐rhodium Migration Reactionsmentioning
confidence: 99%
“…The reaction was monitored by D 2 O quenching. With BINAP as a ligand, the reaction gave aryl‐D product 80 with 99% selectivity; meanwhile, the formation of vinyl‐D product 79 was favored with ligand (1 Z ,5 Z )‐cycloocta‐1,5‐diene (COD) (Scheme ) . It was reasoned that the transmetallation of M59 with ZnCl 2 would give M60 , a product without undergoing 1,4‐Rh migration when COD was used as the ligand.…”
Section: 4‐rhodium Migration Reactionsmentioning
confidence: 99%
“…The results on the deuterium quenching studies clearly demonstrate that alkylzinc 3 a and arylzinc 4 a were produced by the Rh-catalyzed arylzincation of 1 a. Based on the reaction pathways reported for Rh-catalyzed arylation of alkynes [6,7,12] and cyclization reactions, [9a-c] addition of an aryl-Rh intermediate to alkyne in 1 a followed by addition of the resulting alkenyl-Rh A to alkene generates the alkyl-Rh intermediate B. Transmetalation between B and ZnCl 2 [10] produces alkylzinc 3 a and a Cl-Rh species, the latter undergoing the reaction with ArZnCl regenerating aryl-Rh species. When the regiochemistry at the arylrhodation of alkyne is opposite, the alkenyl-Rh intermediate C cannot participate in the intramolecular addition to alkene.…”
Section: Organozincsareorganometallicreagentsconvenientlyusedmentioning
confidence: 98%
“…If the ArB(OH) 2 is replaced by ArZnX and the transmetalation with ZnX 2 takes place for the alkyl-Rh intermediate, the overall reaction would be a new type of catalytic carbozincation giving alkylzinc product. During our studies on the arylzincation of carbon-carbon multiple bonds, [3,10] we found that the catalytic asymmetric carbozincation giving chiral alkylzincs shown in Scheme 1 b is realized in the presence of a chiral diene/Rh catalyst and zinc chloride.…”
Section: Organozincsareorganometallicreagentsconvenientlyusedmentioning
confidence: 99%
See 2 more Smart Citations